Pengaruh pembelajaran IPA berbasis EDP ditinjau dari sikap siswa pada coding terhadap kemampuan berpikir kritis - Vinna Ariyani; Pramudya Dwi Aristya Putra (Papanda Publisher, 2026)
This study was motivated by the low critical thinking skills of junior high school students in science learning and the limited application of learning that systematically integrates engineering and programming processes. The study uses a non-equivalent control quasi-experimental design, involving an experimental class that implements EDP-based science learning and a control class without special treatment. The research subjects consisted of 72 students from classes VII B and VII C at SMPN 2 Jember. Primary data included questionnaires on students' attitudes toward coding and pretest-posttest for critical thinking skills, while secondary data were obtained from observations, interviews, and documentation. Data analysis included normality tests, homogeneity tests, and two-way ANOVA tests. The results of the analysis showed that the posttest score of the experimental class (83.03) was higher than that of the control class (76.11). The two-way ANOVA analysis showed a significant difference in critical thinking skills (p = 0.001 < 0.05), and students' attitudes toward coding also contributed significantly to critical thinking skills (p = 0.001 < 0.05). However, there was no significant interaction between EDP-based science learning and students' attitudes toward coding (p = 0.634 > 0.05). This study confirms that EDP-based science learning and students’ positive attitudes toward coding separately contribute to developing critical thinking skills in junior high school students. The implications of this study indicate that EDP-based science learning can be used as an alternative science learning strategy in junior high schools to support the development of critical thinking skills, even without interaction between learning and students’ attitudes toward coding.